Kualitas Dadih Kedelai Dengan Penambahan Sari JerukManis Dan Jambu Biji - Wahyuni, Antrik, Dra. Titik Suryani, M.Sc (2016)
Dadih is a traditional fermented food from West Sumatera made from fresh buffalo milk put into a bamboo then covered with the banana leaf. The fermentation process of dadih lasts for 48 hours till the formation of clot through the role of lactate acid bacterium. The basic material for making can be replaced by the soybean extract, therefore, dadih can be consumed by the sufferer of lactose intolerance. This research aimed at knowing the quality dadih soybean extract with addition of sweet orange extract and guava seen from the levels of protein, calcium levels, color, smell, flavor, texture and the society's acceptance. The method used in this research was Rancangan Acak Lengkap (RAL/Complete Random Design) 2 factor with 8 treatment degrees that was without the addition of fruit sweet orange and guava extract the addition of sweet orange extract and guava extract as much as 22 ml, 24 ml, and 26 ml for every 200 ml of soybean juice. The results of the research showed that the best quality soybean dadih had a proteint content of 12,33 g/ at K5 (addition of 24 ml guava extract) and the calcium content of 4,97 g/ at K3 (addition of 26 ml of sweet orange extract). The most dominant product of dadih was bright pink, having enough flavor of guava, having enough acid taste, having soft texture and the panelists' dominant acceptance liked the addition of 24 ml of sweet orange extract and the addition of 26 ml of guava extract.